Development of a low power NTSC standard colored video/audio television transmitter at VHF-3 and switchable to UHF - Ching, Gilbert S. (1996)
The problem of this project is to make a low power wireless video/audio transmitter with color using the National Television Committee standard to transmit at channel 3 and switchable to a UHF (Ultra High Frequency) channel over a large radius under unobstructed line of sight conditions except for cloud formations. To make it low power, the number of components must be made as few as possible. One modulator was used with a switch to select which channel to transmit instead of two modulators. The output power of the modulator is not high enough to be received by the television therefore it must be amplified. Two paths of monolithic amplifiers and filters were used for the separate channels. Antenna placed on the last stage of both transmitters also makes the signal reach the receiver.
Thesis (B.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: High definition television; Digital video -- Standards; Digital television; Television -- Transmitters and transmission; National Television Committee; NTSC; Ultra High Frequency (UHF).